The Effect Of Magnetic Field Therapy Accompanying Rehabilitation Exercises In The Treatment Of Some Soft Tissue Injuries In The Shoulder Joint - Ahmed , EmadKadhom (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research came in the use of the latest method of physical therapy (magnetic field) for some soft tissue injuries in the shoulder joint because of the importance of this joint in helping individuals to perform their daily duties as the movement of the upper limb depends mainly on the safety and effectiveness of this joint and the study aimed to identify The effect of physical therapy (magnetic field) associated with rehabilitative exercises in the treatment of some soft tissue injuries in the shoulder joint and the researcher used The experimental approach in the style of designing the individual station is equivalent, and the research sample included a number of patients with soft tissue injuries (muscles, ligaments) with partial tears, and their number was (8) injured from different activities and games, and field research procedures included conducting experiments and tests that included (pain degree, muscular strength , the kinetic range of the shoulder joint in dimensions, approximation and rotation), and based on the rehabilitation program for the special magnetic field, and after studying the case of the healthy sample by specialized doctors and therapists, the researcher adopted the special program of the device’s programs, which is performed from a lying position on the back, then the device is placed on the shoulder area. The duration of treatment (6 weeks) and the number of rehabilitation units using magnets (18 units), the researcher concluded that the rehabilitation program for exercises The rehabilitation accompanying the magnetic therapy prepared by the researcher has a positive effect on improving the muscular strength and range of motion of the shoulder joint, and the researcher recommends emphasizing the necessity of adopting the program prepared by the researcher that accompanies the magnetic field in physical therapy centers and the necessity of using the strength of the magnetic field to treat other injuries.